Counterion effect on the aggregation of anionic perylene dyes and the influence on carbon nanotube dispersion efficiencies - Backes, Claudia; Schunk, Torsten; Hauke, Frank; Hirsch, Andreas (Journal of Materials Chemistry, 2011)
The effect of alkali metal counterions on the aggregation behaviour of an anionic perylene dye has been investigated by absorption and emission spectroscopy. In the presence of Na aggregation is enhanced leading to a decreased surfactant capability for the dispersion of carbon nanotubes. © The Royal Society of Chemistry 2011.